Remineralization efficiency of herbal products - ALKAN, ELİF; TAĞTEKİN, DİLEK (Bilgin Kültür Sanat Yayınları, 2022)
Dental caries is one of the most common chronic diseases in the world and might cause tooth loss when not treated properly. The concept of modern dentistry aims to prevent the progression of caries with early diagnosis, and to improve the aesthetics and function of the tooth with the remineralization process. Thus, caries lesions without cavity are treated with a noninvasive method (Nagarathana et al., 2015). Demineralization occurs through the leaving of mineral ions in dental hard tissues from hydroxyapatite crystals. Restoring these mineral ions to hydroxyapatite crystals is called remineralization. Both processes take place on the tooth surface and a large number of mineral ions can be lost from hydroxyapatite without deterioration of tooth integrity. As a result of the deterioration of the hydroxyapatite structure, cavities are formed. Demineralization is a reversible process; therefore, partially demineralized hydroxyapatite crystals in teeth can be remineralized (Higham, 2016). Enamel caries diagnosed at the initial stage can be treated by regulating diet, controlling plaque formation, and applying appropriate antibacterial agents, thus, demineralized dental tissue can become remineralized (Guerrieri et al., 2012).